The Effectiveness, cost-effectiveness and acceptability of Community versus Hospital Eye Service follow-up for patients with neovascular age-related macular degeneration with quiescent disease (ECHoES) : a virtual randomised balanced incomplete block trial /: a virtual randomised balanced incomplete block trial. (October 2016) - Reeves, B. C
No abstract available